UMP-EV electrical car the speed champ - UMP, PNC
Universiti Malaysia Pahang (UMP) successfully built an environmental-friendly electrical car for the Proton Green Mobility Challenge (PGMC) organised by PROTON Holdings Berhad (PROTON) and Malaysia Innovation Agency (MIA) last October 1, 2012.